Diary of a wimpy kid the third wheel - Kinney, Jeff (Puffin Books London, 2014)
A Valentine's Day dance at Greg's school has turned his world upside down. As Greg scrambles to find a date, he's worried he'll be left out in the cold on the big night. His best friend, Rowley, doesn't have any prospects either but that's small consolation. Then an unexpected twist gives Greg a partner for the dance and leaves Rowley the odd man out. A lot can happen in one night, and in the end, you never know who's going to be lucky in love